Comparison of the ultraviolet-visible spectra of the copper(II) complexes of bidentate Schiff base ligands - Akkus, ÖN; Uzman, S (MARCEL DEKKER INC, 2000)
The bis(salicylaldiminato)copper(II) complexes of the ligand series of salicylaldimines derived from the condensation of n-alkyl or n-alkyloxy substituted aromatic amines with 2,4-dihydroxybenzaldehyde were synthesized. A series of Schiff base ligands with the general formula 4-X-N-(2,4-dihydroxybenzylidene)-aniline and differing only in substituents were synthesized. Some of these compounds have already been reported in literature. X=OCH3[1]OC2H5[2],C4H9[1]. The copper(II) complexes of these ligands having the general formula, copper,bis[o-CN-(p-X-phenyl)-formimidoyl]-4-hydroxyphenolato] were also synthesized. The ligands and their complexes, a total of 24 in number, are studied systematically with ultraviolet-visible spectroscopy to examine the effect of various n-alkyl- and n-alkyloxy substituents on the ligands and on their complexes. In the electronic spectrum of these compounds, the bands observed in the 200-450 nm region which involve charge transfer pi-pi* transition were interpreted.
Keywords: Schiff bases; imine; copper complexes; salicylaldimines; ultraviolet-visible spectroscopy; CRYSTALLINE; Spectroscopy